Preparation of compost using layer droppings with different materials - Khatun, H; Alam, F; Hashem, MA; Rahman, SME (Bangladesh Journal of Animal Science, 2013)
The experiment was carried out by anaerobic composting with layer droppings (T1), layer droppings with straw (T2), layer droppings with fodder residues (T3) and layer droppings with saw dust (T4) under soil surface to study the suitable method with layer droppings and their nutrient composition. The sample from composted materials was collected at 0, 10, 20 and 30 d for proximate analysis. In 30 d of composting dry matter and organic matter were gradually decreased in every method and which were also differed among the treatments (p<0.01). Crude protein (CP) gradually increased in every method and was higher in T3 (19.43%) and then T1 (18.93%), T4 (15.99%) and T2 (14.61%) (p<0.01) at 20 d of composting. The crude fiber content gradually decreased in every method and was higher in T2 followed by T4, T1 and T3 (p<0.01) considerably with the composting period. Ash content was increased in all treatments with the advancing of composting period (p<0.01). The C/N ratio was higher in T4 (22.4) followed by T2 (22.2), T1 (22.0) and T3 (21.9) (p<0.01) considerably with the composting period. The PH value in all treatments decreased up to first ten days then gradually increased with the increase of composting period. The pH value was higher in T1 (8.54) followed by T2 (8.15), T3 (8.10) and T4 (8.00) (p<0.01) at 30 d of composting period. The proximate compositions of all treatments were in acceptable range up to the end of composting period. Therefore, the results suggest that composting layer droppings with fodder residues improve the nutritional value of compost at 20d of composting time. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14131 Bang. J. Anim. Sci. 2012. 41 (2): 120-123